Pengaruh Green Marketing dan Corporate Social Responsibility Terhadap Brand Image pada Produk Tupperware di Kota Padang - Yunfajri Rahma Nofiasari; Yasri Yasri (Jurnal Kajian Manajemen dan Wirausaha, 2019)
The purpose of this researches are to analyze: (1) The effect of green marketing on brand image of Tupperware products in Padang, (2) The effect of corporate social responsibility on brand image of Tupperware products in Padang, (3) The effect of green marketing on corporate social responsibility of Tupperware products in Padang. This type of research is descriptive research. The population in this study of all Tupperware’s customer in Kota Padang. The sample used was 150 respondent using accidental sampling technique. Data was collected through questionnaires and analyzed using the SmartPLS 3.2.7 program. The results of this study indicate that:1) Green Marketing has positive and significant effect on Brand Image products Tupperware in Kota Padang, 2) Corporate Social Responsibility has positive and significant effect on Brand Image products Tupperware in Kota Padang, 3) Green Marketing has positive and significant effect on Corporate Social Responsibility products Tupperware in Kota Padang. Keywords: Green Marketing, Corporate Social Responsibility, Brand Image